Controlled trial of hypnotherapy for weight loss in patients with Obstructive Sleep Apnoea (OSA) - Stradling, J; Roberts, D; Wilson, A; Lovelock, F (1997)
The main cause of OSA is upper body obesity. Despite this, most patients do not lose sufficient weight to get off nasal continuous positive airway pressure (CPAP). In a controlled trial we have explored the use of hypnotherapy, in conjunction with modern dietary advice, in helping OSA patients already on CPAP to lose weight. Hypnotherapy was given in two sessions, a month apart, by an experienced medical hypnotherapist. This was accompanied either by stress reduction strategies, or by suggestions designed to promote reduced calorie intake. An audiotape was provided for continued use at home. Dietary advice was given on two occasions, a month apart, by an experienced dietician, supplemented by appropriate literature. Sixty CPAP patients were randomly assigned to three experimental groups:- dietary advice alone, dietary advice plus hypnotherapy aimed at stress reduction, and dietary advice plus hypnotherapy aimed at calorie reduction. Weights were measured at 1, 3, 6, 9, 12, 15 and 18 months. Analysis of Variance (ANOVA) was used to compare the %weight lost in the three groups. 14 out of 60 patients (25%) railed to complete (5,5 and 4 in the three groups). Initial Body Mass Index was 39.2 (SD6.8) kg/m2. When analysed separately, only the hypnotherapy/stress reduction group maintained a significant, but small, weight loss at 18 months (P<0.02, 3.8 (SD5.8) kg). ANOVA of the three groups showed no significant difference at any one time point, but using the 'area under the curve' (which considers the whole time period) indicated that hypnotherapy with stress reduction produced significantly more weight loss that the other two treatment arms (P<0.003), which were not significantly different from each other. This weight loss trial, conducted in an NHS setting on patients with OSA using CPAP, has shown a small, statistically significant, benefit from adding hypnotherapy (aimed at stress reduction) to conventional dietary advice.